(untitled) (diségno, 2022)
Since the invention of printing, typefaces simulate the appearance of two writing procedures closely linked to manual skills: the uppercase of stone inscriptions and the lowercase of humanistic calligraphy. Typography was born with an ‘original sin’, which numerous treatise writers take care to legitimize through rigorous geometric constructions to support the graphic design of each letter. From the Renaissance to the twentieth century, the evolution of styles and printing techniques is slow, and even the figurative avant-gardes have proceeded in small steps: typographic design is a conservative art, it prefers to emulate or refine previous experiences rather than innovate. In the sixties of the twentieth century, photocomposition dematerializes the techniques of engraving and casting, inducing some designers to experiment with shapes that are easily adaptable to the row-column system. Twenty years later, the Post- Script revolution and the spread of vector software based on spline curves bring drawing fonts closer to manual skills. By hybridizing tradition and experimentation, font design opens to the countless possibilities offered by new media.